Early versus late Gamma Knife radiosurgery for Cushing's disease after prior resection: results of an international, multicenter study - Bunevicius, Adomas; Kano, Hideyuki; Lee, Cheng-Chia; Krsek, Michal; Nabeel, Ahmed M; El-Shehaby, Amr; Abdel Karim, Khaled; Martinez-Moreno, Nuria; Mathieu, David; Lee, John Y K; Grills, Inga; Kondziolka, Douglas; et al. (Journal of neurosurgery, 2021)
OBJECTIVE: The optimal time to perform stereotactic radiosurgery after incomplete resection of adrenocorticotropic hormone (ACTH)-producing pituitary adenoma in patients with Cushing's disease (CD) remains unclear. In patients with persistent CD after resection of ACTH-producing pituitary adenoma, the authors evaluated the association of the interval between resection and Gamma Knife radiosurgery (GKRS) with outcomes. METHODS: Pooled data from 10 institutions participating in the International Radiosurgery Research Foundation were used in this study. RESULTS: Data from 255 patients with a mean follow-up of 65.59 ± 49.01 months (mean ± SD) were analyzed. Seventy-seven patients (30%) underwent GKRS within 3 months; 46 (18%) from 4 to 6 months; 34 (13%) from 7 to 12 months; and 98 (38%) at > 12 months after the resection. Actuarial endocrine remission rates were higher in patients who underwent GKRS ≤ 3 months than when treatment was > 3 months after the resection (78% and 65%, respectively; p = 0.017). Endocrine remission rates were lower in patients who underwent GKRS at > 12 months versus ≤ 12 months after the resection (57% vs 76%, respectively; p = 0.006). In multivariate Cox regression analyses adjusted for clinical and treatment characteristics, early GKRS was associated with increased probability of endocrine remission (hazard ratio [HR] 1.518, 95% CI 1.039-2.218; p = 0.031), whereas late GKRS (HR 0.641, 95% CI 0.448-0.919; p = 0.015) was associated with reduced probability of endocrine remission. The incidence of some degree of new pituitary deficiency (p = 0.922), new visual deficits (p = 0.740), and other cranial nerve deficits (p = 0.610) was not significantly related to time from resection to GKRS. CONCLUSIONS: Early GKRS is associated with an improved endocrine remission rate, whereas later GKRS is associated with a lower rate of endocrine remission after pituitary adenoma resection. Early GKRS should be considered for patients with CD after incomplete pituitary adenoma resection.
Keywords: dospělí; Adrenocorticotropic Hormone; senioři nad 80 let; retrospektivní studie; Humans; následné studie; lidé středního věku; Reoperation; Middle Aged; Aged, 80 and over; Young Adult; mladý dospělý; Follow-Up Studies; radiochirurgie; mužské pohlaví; hypersekrece ACTH v hypofýze; Adult; pituitary surgery; Adolescent; stereotactic radiosurgery; výsledek terapie; Cushing’s disease; Pituitary ACTH Hypersecretion; Postoperative Complications; remission; Treatment Outcome; Pituitary Neoplasms; ženské pohlaví; pooperační komplikace; nádory hypofýzy; reoperace; lidé; adrenokortikotropní hormon; mladiství; adenom; Adenoma; dítě; Child; Aged; Radiosurgery; senioři; Male; Retrospective Studies; Female